Information Transmission across European Equity Markets During Crisis Periods. (6th August 2018) - Chen, Jing; McMillan, David G.; Buckle, Mike
Abstract : To respond to the market turmoil following the demise of Lehman Brothers in September 2008, the majority of European countries imposed short‐selling restrictions on their equity markets. Such a regulatory intervention is likely to have impact on the price formation process and information transmission between markets. We find that the long‐run cointegrating relation between the high‐ and low‐risk country groups in Europe broke down as the crisis emerged and the regulatory remedy failed to correct this. Furthermore, we find the information transmission between markets has reversed from the high‐risk to low‐risk markets in the period following the Lehman demise and imposition of the ban. Further, we notice a similar reversal in the spillover of both return and volatility processes between the different risk‐level country groups. We, therefore, conclude that, overall, the 2008 short‐selling ban had an adverse impact on information transmission between the identified country portfolios in both the long and short run. Notably, the ban did not restore the pre‐crisis transmission channels.